Donor-Derived Cell-Free DNA Testing in Solid Organ Transplantation: A Value Proposition. (23rd May 2020) - Oellerich, Michael; Christenson, Robert H; Beck, Julia; Schütz, Ekkehard; Sherwood, Karen; Price, Christopher P; Keown, Paul A; Walson, Philip D
Abstract: Background: There is a need to improve personalized immunosuppression in organ transplantation to reduce premature graft loss. More efficient biomarkers are needed to better detect rejection, asymptomatic graft injury, and under-immunosuppression. Assessment of minimal necessary exposure to guide tapering and to prevent immune activation is also important. Donor-derived cell-free DNA (dd-cfDNA) has become available for comprehensive monitoring of allograft integrity. A value proposition concept was applied to assess the potential benefits of dd-cfDNA to stakeholders (patient, transplant physician, laboratory medicine specialist, hospital management, insurance companies) involved in solid organ transplantation care. Content: There is robust clinical evidence from more than 48 published studies supporting the role of dd-cfDNA for monitoring graft integrity and detection or exclusion of rejection. The value proposition framework was used to evaluate published key evidence regarding clinical validity, economic implications, and limitations of this approach. It has been shown that dd-cfDNA testing is essential for guiding earlier transplant injury intervention with potential for improved long-term outcome. Summary: Monitoring dd-cfDNA offers a rapid and reproducible method to detect graft injuries at an early actionable stage without protocol biopsies and allows for more effective personalized immunosuppression. The appropriate use of dd-cfDNA testing can provide both clinical and economic benefits to all transplantation stakeholders.